Inventory for Critical Managerial Soft Skills (ICMS) – Development and Standardisation - Chandra Vadhana Radhakrishnan; K.A. Zakkariya (European Scientific Journal, ESJ, 2022)
Purpose: This paper presents the findings of a group of empirical studies for a conceptual and theoretical validation of the Critical Managerial Soft Skills (CMS) Model and then presents the psychometric properties of a newly developed tool - The Inventory for Critical Managerial Soft Skills (ICMS) for assessing the same. Design/methodology/approach: The CMS model was validated by a set of qualitative and quantitative studies among employers to confirm the importance of soft skills and to derive the critical soft skills framework (N- 95, 206) and this served as a basis of the tool construction. ICMS has been then psychometrically validated for the group of management graduates by conducting a series of qualitative and quantitative research steps (N-975). Findings: ICMS is a self-reported scale for measuring seven critical managerial soft skills of managerial candidates namely, Communication skills, Leadership skills, Interpersonal and Teamwork skills, and Self-Management Skills, Decision-making skills, Goal setting skills, and Task efficacy. Research limitations/implications: The tool developed is limited to the measurement of only the seven dimensions which are derived as “critical” based on various stages of the work. Practical implications: The tool can be used for recruitment screening and as a pre and post-training assessment tool for soft skills development of management students.  Social implications: The tool can be used during management education to help the students understand their levels of soft skills and accordingly suitable measures can be undertaken to improve upon during the course of study to enhance their employability. Originality/value: The tool is fully original and has highly useful for researchers and practitioners as it has been empirically validated using appropriate and adequate statistical measures.